2015
DOI: 10.1039/c5ra22704f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the catalytic performance of cobalt oxide by doping on ceria in the high temperature water–gas shift reaction

Abstract: The high temperature water–gas shift (HT-WGS) reaction was performed using a Co–CeO2 catalyst, prepared through a co-precipitation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…This effect can be attributed to the particle size enhancement in Mo‐Co 3 O 4 , as the Raman peak intensity is dependent on the grain size of the material . Doping molybdenum produced Raman peak shifts to a higher energy compared to that of pure Co 3 O 4 , as a result of lattice deformation …”
Section: Discussionmentioning
confidence: 99%
“…This effect can be attributed to the particle size enhancement in Mo‐Co 3 O 4 , as the Raman peak intensity is dependent on the grain size of the material . Doping molybdenum produced Raman peak shifts to a higher energy compared to that of pure Co 3 O 4 , as a result of lattice deformation …”
Section: Discussionmentioning
confidence: 99%
“…[ 123 ] At a structural level, there should be changes in the atomic environment of the parent CeO 2 structure after substitution of metal ions. [ 126 ] It was concluded that the doping of the ceria sub-lattice with Co 2+ ions allowed for the accommodation of more oxygen vacancies/defect sites compared to the pure ceria, and thus enhancing the redox properties of the resulting mixed oxide, which was supported by Raman spectra and hydrogen-temperature programmed Adv. [ 124 ] In this sense, a doped transition metal can introduce stress into the lattice of ceria, which in turn decrease the oxygen vacancy formation energy resulting in greater nonstoichiometry, leading to enhancement of the OSC and catalytic activity.…”
Section: Modulation the Defects Or Oxygen Vacancies Of Ceria Nanomatementioning
confidence: 90%
“…[ 126 ] Furthermore, our group presented a facile method to engineer the anti-oxidation performance of CeO 2 nanoparticles through the modifi cation of the defect state and reducibility by doping with Gd(III) cations. [ 126 ] Furthermore, our group presented a facile method to engineer the anti-oxidation performance of CeO 2 nanoparticles through the modifi cation of the defect state and reducibility by doping with Gd(III) cations.…”
Section: Modulation the Defects Or Oxygen Vacancies Of Ceria Nanomatementioning
confidence: 99%
“…Co 2p XP spectra of CC773 and CMC773 samples are illustrated in Figure b. It can be seen from the Figure that the spectra is composed with two main peaks situated at around ∼780.2 and ∼795.0 eV assigned to Co 2p 3/2 and Co 2p 1/2 regions, respectively . Furthermore, the Co 2p 3/2 region is split into two major peaks located at 780.5±0.4 and 781.8±1.2 eV, which can be attributed to Co 3+ and Co 2+ ions, respectively for both the samples.…”
Section: Resultsmentioning
confidence: 98%
“…This is due to the fact that the strong interaction between the manganese and ceria facilitates to improve the reducibility of the samples. On the other hand, for Co doped CeO 2 (CC773) sample, the first peak at ∼425 K is assigned to the reduction of Co 3+ to Co 2+ and the second peak around ∼634 K is caused by the reduction of surface oxygen of ceria, respectively . However, the surface Ce +4 to Ce 3+ reduction in Co doped CeO 2 (CC773) catalyst is observed at lower temperature compared to C773 and Mn doped CeO 2 (CMM773).According to the literature, it can be stated that the coexistence of CeO 2 and CoO x can mutually promote each other's reduction by enhancing the mobility of oxygen species .…”
Section: Resultsmentioning
confidence: 99%